Managing the nexus for Green Growth - Bezençon, Valéry; Leflaive, X.; Maitra, S.; Krishnaswamy, R.; Stuchtey, M.; Waughray, D. (Rio 2012 process German Goverment in Bonn, 2011)
Bezençon, V, , S. Maitra, R. Krishnaswamy, M. Stuchtey, D. Waughray
, Background paper for the conference